Synthesis, crystal structure, spectral properties and catalytic activity of binuclear copper(II), mononuclear nickel(II) and cobalt(III) complexes containing Schiff base ligand - Pattanayak, Poulami
Newly designed tridentate ligand, HL 1 derived from 2-(benzylthio) aniline and 2-hydroxy-1-naphthaldehyde, upon reaction with Cu(II), Ni(II) and Co(III) nitrate separately in methanol yielded binuclear Cu(II) complex, [Cu-2(L)(2)(NO3)(2)](2), and mononuclear [Ni(L)(2)] 3 and [Co(L)(2)](NO3) 4 which were characterized by spectral data and authenticated by single crystal X-ray diffraction of 2 and 3. The diffraction analysis revealed that the ligand binds to metals in (O, N, S) fashion. Single crystal X-ray diffraction studies confirmed that the [Cu-2(L)(2)(NO3)(2)] complex consist of centrosymmetric binuclear entities containing square-pyramidal copper(II) ions bridged through the phenoxo oxygen atoms. The emission and redox properties of both the ligand and corresponding complexes were examined. The redox property of the complexes has been qualitatively explained by single point DFT calculations. The catalytic activities of Cu(II) complex [Cu-2(L)(2)(NO3)(2)] towards oxidation of benzyl alcohol derivatives to carbonyl compounds was tested using H2O2 as the oxidant. (C) 2014 Elsevier B. V. All rights reserved.